2012
DOI: 10.1097/prs.0b013e318262f38a
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Intercostal Artery Perforator Flap Autologous Augmentation in Bariatric Mastopexy

Abstract: The anterior intercostal artery perforator flap proved to be a reliable option in bariatric mastopexy. The technique can be performed easily and allows the harvesting of a large amount of tissue with a wide range of motion, providing adequate breast volume and projection without the need for implant placement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…AICAP flaps are based on perforators originating from the rectus abdominis or oblique segment of the intercostal artery. 8 , 10 Cadaveric studies 11 and radiological studies 7 , 12 have demonstrated reliable and consistent location of perforator arteries.…”
Section: Discussionmentioning
confidence: 92%
“…AICAP flaps are based on perforators originating from the rectus abdominis or oblique segment of the intercostal artery. 8 , 10 Cadaveric studies 11 and radiological studies 7 , 12 have demonstrated reliable and consistent location of perforator arteries.…”
Section: Discussionmentioning
confidence: 92%
“…Intercostal perforators have not been traditionally described to emanate from the lower anterior abdomen nor have they been utilized for lower extremity defects. However, their use for soft tissue recruitment has been well documented including repair of: upper extremity, epigastric, breast, and back defects . Multiple branch patterns of the intercostals system with named perforators: dorsal, lateral, and anterior intercostals perforator arteries traditionally serve as the sources of pedicled flaps.…”
Section: Discussionmentioning
confidence: 99%
“…However, their use for soft tissue recruitment has been well documented including repair of: upper extremity, epigastric, breast, and back defects . Multiple branch patterns of the intercostals system with named perforators: dorsal, lateral, and anterior intercostals perforator arteries traditionally serve as the sources of pedicled flaps. Description of intercostals perforators have mostly been restricted to the 4th–8th penetrating vessels, where cases describing penetrating 10th, 11th, and 12th vessels are rare .…”
Section: Discussionmentioning
confidence: 99%
“…There are many conventional flaps, mostly musculocutaneous flaps defined to be used in truncal defects, but perforator flap concept has been recently utilized (Hamdi et al, ; Iida et al, ). Deep inferior epigastric artery perforator (DIEP) flap and thoracodorsal artery perforator (TAP) flap has gained popularity in breast reconstruction, while lateral thoracic artery perforator (LTAP) flap has been recently reported to be used in locoregional reconstruction (Hwang, Kim, Kim, & Kim, ; Persichetti et al, ). Intercostal artery perforator flaps originating from anterior, lateral and posterior branches of intercostal arterial network have been reported to be useful in reconstructing defects of various size (Baghaki, Cevirme, Diyarbakirli, Tatar, & Aydin, ; McCulley, Schaverien, Tan, & Macmillan, ).…”
Section: Introductionmentioning
confidence: 99%